ANALISIS REAKSI PASAR TERHADAP PENGUMUMAN PERGANTIAN CHIEF EXECUTIVE OFFICER (CEO) - , NOVYANDRI TAUFIK BAHTERA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper examines the market reaction to CEO turnover announcements measured by abnormal return. The samples consist of 55 CEO turnover announcements by using t-test to examine information content of those announcements. The author classifies turnover into two factors: (1) the process of turnover (routine and non routine) and (2) the origin of successor (inside and outside). Market reacts significantly positive to the turnover announcements of routine CEO who are from inside. Differences in reaction occur on turnover announcements of routine outside and non routine inside CEO responded negatively significant. Market does not react to announcement of non-rutine outside CEO turnover. The results show that investors in Indonesia react positively to routine inside CEO turnover because investors believe that a new CEO will continue the stategy and leadership style as well as having a lower level of uncertainty. Negative reaction to routine outside CEO turnover due to market does not convince that the successor will sustain the strategy of the previous CEO and has a high degree of uncertainty. The cause of negative market reaction to announcement of non-routine inside CEO turnover is the successor CEO will continue the old style of leadership and are jointly responsible for the poor performance of company.